2013
DOI: 10.1002/jgrd.50636
|View full text |Cite
|
Sign up to set email alerts
|

Horizontal water vapor transport in the lower stratosphere from subtropics to high latitudes during boreal summer

Abstract: We compare global water vapor observations from Microwave Limb Sounder (MLS) and simulations with the Lagrangian chemical transport model CLaMS (Chemical Lagrangian Model of the Stratosphere) to investigate the pathways of water vapor into the lower stratosphere during Northern Hemisphere (NH) summer. We find good agreement between the simulation and observations, with an effect of the satellite averaging kernel especially at high latitudes. The Asian and American monsoons emerge as regions of particularly hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
221
0
1

Year Published

2014
2014
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 140 publications
(247 citation statements)
references
References 87 publications
22
221
0
1
Order By: Relevance
“…This poleward transport is caused by advection by the residual circulation equatorward of about 40 • and by eddy mixing poleward. Recently, Ploeger et al [2013] found a similar latitudinal separation for the local effects of residual circulation and eddy mixing on horizontal water vapor transport. The enhanced vertical gradient in the local residual circulation effect around 500 K (∼20 km) and the strong horizontal gradient around 40 • N/S indicate the separation of a shallow circulation branch from the deep branch above [compare Birner and Bönisch, 2011].…”
Section: Ploeger Et Almentioning
confidence: 60%
See 1 more Smart Citation
“…This poleward transport is caused by advection by the residual circulation equatorward of about 40 • and by eddy mixing poleward. Recently, Ploeger et al [2013] found a similar latitudinal separation for the local effects of residual circulation and eddy mixing on horizontal water vapor transport. The enhanced vertical gradient in the local residual circulation effect around 500 K (∼20 km) and the strong horizontal gradient around 40 • N/S indicate the separation of a shallow circulation branch from the deep branch above [compare Birner and Bönisch, 2011].…”
Section: Ploeger Et Almentioning
confidence: 60%
“…The Lagrangian transport model CLaMS has been shown to simulate the global stratospheric trace gas distributions well and even the small-scale structures and steep gradients therein [e.g., Konopka et al, 2004]. In particular, the multiyear simulation analyzed here has been shown to realistically represent transport of ozone and water vapor in the lower stratosphere [e.g., Konopka et al, 2010;Ploeger et al, 2013]. The mean age of air in the model is calculated from a "clock tracer" [e.g., Hall and Plumb, 1994;Waugh and Hall, 2002], a synthetic species with linearly increasing mixing ratio in the lowest model layer (orography following) and without any sources or sinks above.…”
Section: Age Of Air Simulation and Observationsmentioning
confidence: 99%
“…Comprehensive analyses of transport processes from the troposphere into the stratosphere and tracer proportions of the extratropical UTLS region have been published (e.g. Hegglin et al, 2009;Hoor et al, 2010;Ploeger et al, 2013). Rossby wave breaking (Ploeger et al, 2013) and midlatitude overshoot convection (Dessler, 2009) result in the transport and mixing of air masses into the extratropical UTLS on short timescales (weeks).…”
Section: R Spang Et Al: Satellite Observations Of Cirrus Clouds In mentioning
confidence: 99%
“…Hegglin et al, 2009;Hoor et al, 2010;Ploeger et al, 2013). Rossby wave breaking (Ploeger et al, 2013) and midlatitude overshoot convection (Dessler, 2009) result in the transport and mixing of air masses into the extratropical UTLS on short timescales (weeks). On seasonal timescales, downwelling by the deep Brewer-Dobson circulation branch moistens the extratropical UTLS at altitudes above 450 K (Ploeger et al, 2013).…”
Section: R Spang Et Al: Satellite Observations Of Cirrus Clouds In mentioning
confidence: 99%
See 1 more Smart Citation